Prognostic value of systemic immune-inflammation index in patients with metastatic renal cell carcinoma treated with systemic therapy: a meta-analysis - Xu, Juan; Chen, Pingrun; Cao, Shangqi; Hu, Xu; Li, Xiang (Frontiers in Oncology, 2024)
Objective A novel systemic immune-inflammation index (SII), based on the neutrophils, lymphocytes, and platelet counts, is associated with the prognosis of several cancers, including non-metastatic renal cell carcinoma (RCC). In the present study, we evaluate the prognostic significance of SII in patients with metastatic RCC (mRCC) treated with systemic therapy. Method Relevant studies were searched comprehensively from Web of Science, PubMed, Embase and the Cochrane Library up to January 2024. The pooled hazard ratio (HR) and 95% confidence interval (CI) were extracted from each study to evaluate the prognostic value of SII in patients with mRCC treated with tyrosine kinase inhibitor (TKI) or immune checkpoint inhibitor (ICI). Results A total of 12 studies including 4,238 patients were included in the final analysis. High SII was significantly correlated to poor overall survival (OS, HR = 1.88; 95% CI 1.60–2.21; P < 0.001) and progression-free survival (PFS, HR = 1.66; 95% CI 1.39–1.99; P < 0.001). Stratified by therapy, high SII was also related to the poor OS (TKI: HR = 1.63, P < 0.001; ICI: HR = 2.27, P < 0.001) and PFS (TKI: HR = 1.67, P < 0.001; ICI: HR = 1.88, P = 0.002). Conclusion In conclusion, high SII could serve as an unfavorable factor in patients with mRCC treated with systemic therapy. Stratified by therapies, the elevated SII was also associated with worse prognosis. Whereas, more prospective and large-scale studies are warranted to validate our findings. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024522831, identifier CRD42024522831.